PENGARUH MODEL PEMBELAJARAN SCIENCE TECHNOLOGY SOCIETY BERMUATAN PENDIDIKAN KARAKTER DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR BIOLOGI - San Selvianus; Eufrasia Jeramat; Apolonia H. Ramda (Unika Santu Paulus Ruteng, 2018)
The purpose of this study aims to find out: (1) Differences in learning outcomes between groups of students studying with STS with character education (STSBPK) and direct learning models (MPL). (2) Interaction of learning models towards learning outcomes concerning learning motivation (MB) students (3) Differences in learning outcomes between groups of students studying with STSBPK and MPL in students who have high MB. (4) Differences in learning outcomes between groups of students studying with STSBPK and MPL in students who have low MB. This study was a quasi-experimental with a 2x2 factorial design with a posttest-only control group design pattern. The subject of this study was class X SMA Budi Dharma Cancar 2016/2017 academic year. The sample amounted to 84 students with the sampling technique using simple random sampling. Learning outcomes data were collected with 40 items of learning outcomes tests while learning motivation data were collected with 38 questionnaire items. The data obtained were analyzed using descriptive statistics and two-way ANOVA.